Assessment of Groundwater Resources in Jhunjhunun District, Rajasthan - Goyal, R K (Annals of Arid Zone, 2016)
An assessment of groundwater resources in Jhunjhunun district during 2005-2008 revealed that about 46% area of the district had water table at >60 m below ground level (bgl). Younger alluvium had a shallower water table (mean depth 40.63 m bgl). Ground water quality in the district is generally good (mean EC 1.88 dS m-1), and is best in the younger alluvium (mean EC 0.78 dS m-1). For irrigation purpose the district’s groundwater could be categorized as having low salinity, medium sodicity and high alkanity (C1S2R2). The discharge from the wells varied from 40 to 120 m3 day-1. Groundwater level in the district has found to be falling at an average rate of 1.46 m y-1 (2001-2008). The net groundwater availability, total draft, groundwater balance and stage of groundwater development were calculated as 274.61 mcm, 525.84 mcm, (-) 251.18 mcm, and 191.5%, respectively. There is, therefore no scope for future groundwater development in the district.